PROBLEMS OF COLLECTING, PRESERVING AND EVALUATING DIGITAL EVIDENCE IN THE INVESTIGATION OF CYBER FRAUD - B. B. Suyunov (International Journal of Business, Law and Political Science, 2026)
Objective: The article examines the problems arising at the three stages of handling digital evidence in the investigation of cyber fraud: their collection, preservation, and evaluation. Method: The institution of digital evidence, introduced into the Criminal Procedure Code of the Republic of Uzbekistan by Law No. ZRU-1003 of 21 November 2024, is subjected to comparative analysis with international standards ISO/IEC 27037, NIST SP 800-86, and SWGDE recommendations. Results: The absence in national legislation of a mechanism for the expedited preservation of electronic data, given their volatility, is identified as the principal problem. Novelty: Proposals for eliminating the absence of an expedited electronic data preservation mechanism are advanced through a comparative analysis of Uzbekistan’s legal framework and international digital evidence standards.